(untitled) (The Planet, 2024)
Background: Cholecystectomy remains one of the most common abdominal surgeries done worldwide and the timing of surgery— elective vs. emergency—continues to be controversial. This study aims to compare postoperative complications between elective and emergency cholecystectomy after adjusting for significant patient and disease factors. Methods & Materials: This observational study included 120 cholecystectomy patients—60 elective and 60 emergency cases. Postoperative complications over 30 days were recorded, including wound infection, bile leak, fever, reoperation, ICU admission, readmission, and mortality. Descriptive statistics compared demographics and intraoperative data, while Cox proportional hazards regression assessed the impact of surgery type on complications, adjusting for confounders. Results: The emergency group experienced notably higher wound infection rates (16.7% vs 5.0%, p=0.04), postoperative fever (25% vs 8.3%, p=0.02), and conversion to open surgery (16.7% vs 1.7%, p=0.01). Hospital stays longer than 5 days were significantly more common for emergency cases (36.7% vs 3.3%, p<0.001). Readmission was four times more likely in the emergency group (13.3% vs 3.3%, p=0.04). On multivariable Cox regression analysis, emergency surgery was the strongest independent predictor of complications (HR=2.45, 95% CI: 1.32-4.55, p=0.004), followed by diabetes (HR=2.10, p=0.02) and age >60 years (HR=1.80, p=0.045). Conclusion: Emergency cholecystectomy is associated with significantly higher postoperative complication rates, increased in-hospital stay, increased likelihood of conversion to open procedure, and increased readmission rates. These findings strongly support early elective surgery for symptomatic gallstones when clinically appropriate to avoid emergency presentations with their associated increased morbidity.